DEVELOPMENT OF SAFETY PERFORMANCE MODEL FOR TOLL ROADS (CASE STUDY: TRANS-JAVA TOLL ROAD CORRIDORS CIKAMPEKâPALIMANAN AND KANCIâSEMARANG) - Hadiyanti, Istyana
Road safety is an important aspect to be considered in road planning, especially for toll roads as paid roads, where road users have the right to get better safety, security, and comfort when driving on toll roads. During 2019-2020 there have been 1,291 single accidents on the Trans-Java toll road sections, the Cikampek– Palimanan and Kanci–Semarang toll roads, which caused quite a lot of fatalities and injuries. Thus, serious efforts are needed to reduce the probability of crashes and the crash severity, especially those related to single crashes as the dominant crash type on the Trans-Java toll road. This study aims to determine factors associated with the frequency of single crashes and the severity of single crashes on toll roads. For this purpose, toll road safety performance models, consisting of a single crash expectation model and a single crash severity prediction model, were developed. The crash expectation model was developed using the Negative Binomial regression model, with crash frequency as the dependent variable and geometric and road environment factors as independent variables. Meanwhile, a single crash severity model was developed using a multinomial logistic regression model. The results show that a higher single crash frequency is associated with higher annual average daily traffic and the absence of a roadside safety barrier. Meanwhile, the lower single crash frequency is associated with the maximum slope value in the 1-km long segment before the road segment under review, the absence of a median safety barrier, the presence of a flexible median safety barrier, and the presence of a bridge pillar. For crash severity, the crash involving an overturned vehicle and the presence of a flexible median safety barrier is associated with an increased probability of fatal and injury crashes. Meanwhile, the presence of a rigid median safety barrier is associated with a lower probability of fatal and injury crashes.